Early Identification of Potentially Drought-Tolerant Doubled Haploid Rice Lines During the Seedling Stage - Munandar, Arief; Purwoko, Bambang Sapto; Dewi, Iswari Saraswati; Suwarno, Willy Bayuardi; Hadianto, Wira; Nurhidayah, Siti (Department of Agronomy and Horticulture, IPB University, 2025)
Climate change and reduced crop yields caused by drought stress have increased the demand for drought-tolerant varieties. The anther culture technique allows the production of improved varieties with high homozygosity in a short time. The study aimed to select the drought-tolerant double haploid lines at the seedling stage. This research was conducted in the greenhouse of the Indonesian Center for Agricultural Biotechnology and Genetic Resources Instrument Standard Testing (BBPSI Biogen), Bogor, from August to November 2023. The drought-tolerant selection of 12 doubled-haploid rice lines (AE1-AE12) and four check varieties, i.e., two commercial checks (“Inpari 18” Tadah Hujan Agritan or AE13, “Bioni63” Ciherang Agritan or AE14), one drought-tolerant check (“Salumpikit” or AE15), and one drought-sensitive check (“IR20” or AE16). The research used a randomized complete block design with three replications. The characters observed were leaf rolling, leaf drying, recovery ability, and plant fresh and dry weight. The Friedman test results showed that the lines with the lowest rankings, three lines (AE2, AE5, and AE12) with mild tolerant criteria for leaf rolling, five lines (AE1, AE2, AE5, AE8, and AE12) with mild tolerant criteria for leaf drying, and three lines (AE1, AE5, and AE12) with tolerant criteria for recovery ability. The selection index for drought tolerance at the seedling stage identified seven lines with positive values. Based on the Friedman test, selection index, and heatmap visualization, AE12, AE1, AE5, and AE8 exhibited a tolerance similar to “Salumpikit” and were deemed suitable based on drought tolerance characters.